Climate-smart agriculture reduces capital-based livelihoods vulnerability: Evidence from Latin America - Martínez-Barón, Deissy; Alarcón de Antón, Marina; Martinez Salgado, Jesús David; Castellanos, Andrea Estefanía (Frontiers Media, 2024)
Introduction: Climate change poses a significant threat to rural livelihoods in low- and middle-income countries. Enhancing the sustainability of these livelihoods is crucial for ensuring food security and nutrition at both global and regional levels. This study investigates the role of Climate Smart Agriculture (CSA) practices in improving rural livelihoods in Latin America, specifically through the Climate Smart Village (CSV) approach.